Implementation of Disaster Education and The Level of Preparedness In Senior High Schools - Fakhrani, Maulida; Nirwansyah, Anang Widhi; Andriani, Ana (Edueksos Jurnal Pendidikan Sosial & Ekonomi, 2025)
This study aims to analyze the implementation of disaster education at SMA Muhammadiyah Zam-zam Banyumas region and determine the level of preparedness of SMA Muhammadiyah Zam-zam Banyumas region in facing disasters. The subjects of this research are students, teachers, and principals. This research uses descriptive qualitative methods with data collection techniques through observation, interviews, and documentation studies. The data obtained was then triangulated to improve the validity of the information. The results showed that disaster material had been integrated into the curriculum, especially geography and physics subjects, and extracurricular activities. However, teachers have not been able to integrate disaster material into history subjects. Furthermore, schools already have supporting facilities such as school health units, evacuation signs, and light fire extinguishers, and carry out incidental disaster simulations. This research also shows that the school still uses a manual system and has not developed a comprehensive emergency response plan document. This study recommends the need to develop emergency response plans, improve disaster warning systems, optimize the integration of disaster material in all subjects, verify supporting facilities, and routine training and simulations.Keywords: Integrated Curriculum, Disaster Material, Senior High School.